THE DISUNITED STATES’ DECOUPLING FROM ITS FORLORN FOREIGN AFFAIRS’ ENTANGLEMENTS - ST. JOHN, ANTHONY (Society Register, 2021)
The short-term ‘reign’ of the United States as leader of the world, policeman of the world, is being seriously challenged not only by pundits all over the world but by even political scientists and analysts in the United States itself. In fact, many are seriously opining that the United States is in decline—that it has lost its sense of direction, has taken itself too seriously, and has led the world for its own profit and well-being while disregarding the realities of other nations and peoples. The article attempts to trace the reasons for this sudden reversal of popularity of the DisUnited States of America.